'Getting angry with honest people': The illicit market for immigrant 'papers' in Cape Town, South Africa. (31st March 2017) - Alfaro-Velcamp, Theresa; McLaughlin, Robert H.; Brogneri, Gahlia; Skade, Matthew; Shaw, Mark
Abstract: South African Department of Home Affairs (DHA) officials 'seem to get angry with honest people', shared a Congolese immigrant from the Kivu region who now resides in Cape Town. Some DHA officials get money through illicit transactions for 'papers' and they become visibly frustrated with immigrants who try to obtain documents by lawful means. While there has been much focus on xenophobia associated with immigration in South Africa, there has been little attention paid to the illicit market in immigrant papers such as asylum seeker permits (Section 22 permits), refugee status permits (Section 24 permits), and work permits. These immigrant documents assist individuals—namely those who otherwise lack status, or 'papers', or both—to obtain abilities to work, travel safely, register themselves or their children for school, access non-emergency healthcare, and gain banking privileges. In providing an account of the market in immigrant papers, the article focuses on how these documents relate to status and survival. By purchasing papers in Cape Town, immigrants (referring to asylum seekers, refugees, and cross border migrants) aim to secure their legal status and gain productive agency in their lives. This paper is based on an ethnographic research methodology and participant observation, and shows how immigration challenges South Africa's post-apartheid, constitutionally-mandated socio-economic rights and democratic aims and has fostered an illicit market in immigrant documents. This work furthers debates on immigration governance in the global south, corruption in state institutions, and the vulnerability of immigrants.